2018
DOI: 10.1021/acs.jnatprod.7b00993
|View full text |Cite
|
Sign up to set email alerts
|

Evodialones A and B: Polyprenylated Acylcyclopentanone Racemates with a 3-Ethyl-1,1-diisopentyl-4-methylcyclopentane Skeleton from Evodia lepta

Abstract: Two polyprenylated acylcyclopentanone racemates, evodialones A (1) and B (2), featuring a 3-ethyl-1,1-diisopentyl-4-methylcyclopentane skeleton, were isolated from an extract of the aerial parts of Evodia lepta. Evodialone A (1) was resolved by chiral-phase HPLC to afford a pair of enantiomers, (+)- and (-)-evodialones A (1b/1a), while evodialone B (2) could not be resolved. Their structures were elucidated by spectroscopic analysis and a combination of computational techniques including gauge-independent atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…To define the absolute configurations of the individual enantiomers of 1 , the experimental ECD curves of (+)- 1 and (−)- 1 were compared with those calculated by using the time-dependent density functional theory (DFT) approach. As illustrated in Figure , the calculated ECD spectra of (3 R ,5 R ,16 R )- 1 and (3 S ,5 S ,16 S )- 1 agreed well with the experimental curves of (+)- 1 and (−)- 1 , respectively, which was consistent with reported data . The modified Mosher’s method was applied to confirm the absolute configuration of (−)- 1 . , Esterification of (−)- 1 with ( R )- and ( S )-α-methoxy-α-(trifluoromethyl)­phenylacetyl chloride (MTPACl) gave the corresponding (16 S )- and (16 R )-MTPA esters, respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…To define the absolute configurations of the individual enantiomers of 1 , the experimental ECD curves of (+)- 1 and (−)- 1 were compared with those calculated by using the time-dependent density functional theory (DFT) approach. As illustrated in Figure , the calculated ECD spectra of (3 R ,5 R ,16 R )- 1 and (3 S ,5 S ,16 S )- 1 agreed well with the experimental curves of (+)- 1 and (−)- 1 , respectively, which was consistent with reported data . The modified Mosher’s method was applied to confirm the absolute configuration of (−)- 1 . , Esterification of (−)- 1 with ( R )- and ( S )-α-methoxy-α-(trifluoromethyl)­phenylacetyl chloride (MTPACl) gave the corresponding (16 S )- and (16 R )-MTPA esters, respectively.…”
Section: Resultssupporting
confidence: 87%
“…Their structures were identified as rearranged acetophenones having a prenylated acylcyclopentenone scaffold, by analysis of spectroscopic data (1D, 2D NMR) and comparison with literature values (Table S1, Supporting Information). The lack of optical activity and Cotton effects in the ECD spectrum indicated that 1 was racemic. Subsequently, 1 was resolved into two enantiomers, (+)- 1 and (−)- 1 , in a ratio of 1:1 by chiral-phase HPLC (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…configs. by a combination of modified Mosher's and TDDFT-ECD methods [200], while 423a/423b and 424 in racemic form had been previ-ously isolated from Evodia lepta by Tang et al in 2018 [201]. Also identified as rearranged acetophenones, compounds 427a/427b coupled with a phenylpropanoid fragment were isolated from Xanthostemon chrysanthus in 2019 [187].…”
Section: Acetophenonesmentioning
confidence: 99%
“…In addition to its medicinal use, it has a long history being used as food, such as in Guangdong herbal tea [ 13 ]. The fat-soluble components of E. lepta [ 14 ], e.g., volatile oil, alkaloids, flavonoids, and coumarins, showed good anti-inflammatory [ 15 ], anti-viral [ 16 ], anti-bacterial [ 17 ], and antitumor [ 18 ] activities. Interestingly, the total sugar content of E. lepta is more than 30%, with oligosaccharides appearing to be the main active ingredients.…”
Section: Introductionmentioning
confidence: 99%